Prevalence of corrected arterial hypertension based on the self-reported prevalence estimated by the Brazilian National Health Survey - Jessica Pronestino de Lima Moreira; Renan Moritz Varnier Rodrigues de Almeida; Nei Carlos dos Santos Rocha; Ronir Raggio Luiz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
The objective was to correct the self-reported prevalence of systemic arterial hypertension (SAH) obtained from the Brazilian National Health Survey (PNS 2013). SAH prevalence estimates were corrected by means of sensitivity/specificity of information. Sensitivity and specificity values from a similar study (same self-report question, age range and gold standard) were used to this end. A sensitivity analysis was also performed, by using the upper and lower limits of confidence intervals as sensitivity and specificity parameters. The corrected prevalence of SAH for Brazil as a whole was 14.5% (self-reported: 22.1%). Women presented a higher rate of self-reported SAH but, after correction, men were found to have a higher prevalence. Among younger women (18-39 age range), the self-reported prevalence was 6.2%, a value that, after correction, dropped to 0.28%. There was not much difference between self-reported and corrected SAH among the elderly (51.1% vs. 49.2%). For certain groups the corrected results were greatly different from the self-reported prevalence, what may severely impact public health policy strategies.